A MULTIMODAL ANALYSIS OF FRENCH MULTINATIONAL LIPSTICK ADVERTISEMENTS ON YOUTUBE (2024-2025) - Eva Margareth Sylvana Tio; Tri Indri Hardini; Rika Widawati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study analyzes visual and auditory elements in French multinational lipstick advertisements to examine how multimodality constructs brand identity. Although multimodal discourse analysis has been widely applied in advertising studies, limited attention has been devoted to how multinational French cosmetic advertisements construct global beauty identity through the integration of visual and auditory semiotic resources on digital platforms such as YouTube. This study applies the Gunther Kress and Theo van Leeuwen theory of multimodal discourse to understand the interaction between modalities in digital advertisements. This study employed a qualitative descriptive method exploring how individuals interpret social or human issues through inductive analysis and contextual interpretation. Data were drawn from French multinational lipstick advertisements aired on YouTube between 2024 and 2025. This study employed a descriptive qualitative method. The findings reveal that visual (color, background, shooting techniques, models) and auditory (music) modes work synergistically not only to convey product messages but also to construct femininity, elegance, inclusivity, and the globalized image of French beauty ideals, as well as enhance consumer engagement and strengthen brand appeal, exemplified by Dior Lip Glow. The study concludes that multimodal discourse analysis effectively enhances audience appeal and reinforces brand identity in advertising. This study contributes by extending multimodal discourse analysis to French multinational lipstick advertisements, a domain rarely examined.